Developing English Module through Think Pair Share Strategy Based on Riau Local Wisdom in Teaching Reading Comprehension - Jannah, Miftahul; Marleni, Lusi; Sari, Nurhidayah; Hardi, Vitri Angraini (Universitas Pahlawan Tuanku Tambusai, 2024)
Students only rely on national books used by schools issued by the government, many students cannot understand the contents of the book. In addition, foreign materials and vocabulary are not yet known to students. This makes student interest one of the factors in the occurrence of reading problems. Students who have low interest may have difficulty understanding the text. The purpose of writing the research is to develop an English module through the think pair share strategy based on Riau local wisdom in teaching reading comprehension. This study uses (R D) method. The instruments in this study used tests, field notes and interviews as data collection. The sample in this study was class XI Medeka 3 students at SMAN 1 Bangkinang with a total of 26 students. The results of this study showed that before using the module in learning English, the average student score obtained was 75.19. After using the module, the average student score was 81.92. The results of the independent sample test showed that Ho was accepted and Ha was rejected. The conclusion of this study is that there are no significant results in the use of the English reading teaching module.